2021
DOI: 10.1017/s002221512100181x
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal effects of external dacryocystorhinostomy

Abstract: Objective External dacryocystorhinostomy is thought to cause mucociliary dysfunction by damaging the mucosa, in turn affecting ciliary activity and mucus quality. This study investigated the effect of external dacryocystorhinostomy on sinonasal function. Methods Patients scheduled for unilateral external dacryocystorhinostomy who underwent endoscopic nasal examination and paranasal sinus computed tomography were included in this study. A saccharine test was performed on the planned surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The existing surgical methods include lacrimal intubation, YAG laser , external dacryocystorhinostomy (Ex-DCR) and EE-DCR [3][4]. For more than 100 years, Ex-DCR has been regarded as the "gold standard" for the treatment of chronic dacryocystitis, but it can't meet people's growing medical needs due to the shortcomings of facial skin scar, large trauma, affecting the function of "tear pump" and unable to deal with nasal complications at the same time [5][6][7]. Over the past 10 years, with the continuous improvement of endoscopic imaging system, ENT micro power system and other medical equipment, EE-DCR is highly recommended in clinic because of its incomparable advantages of Ex-DCR, such as no facial skin incision, minimally invasive and does not affect the function of "tear pump", simultaneous treatment of nasal complications, et al However, so far, the e cacy of EE-DCR has been reported differently, and its losers are not rare [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The existing surgical methods include lacrimal intubation, YAG laser , external dacryocystorhinostomy (Ex-DCR) and EE-DCR [3][4]. For more than 100 years, Ex-DCR has been regarded as the "gold standard" for the treatment of chronic dacryocystitis, but it can't meet people's growing medical needs due to the shortcomings of facial skin scar, large trauma, affecting the function of "tear pump" and unable to deal with nasal complications at the same time [5][6][7]. Over the past 10 years, with the continuous improvement of endoscopic imaging system, ENT micro power system and other medical equipment, EE-DCR is highly recommended in clinic because of its incomparable advantages of Ex-DCR, such as no facial skin incision, minimally invasive and does not affect the function of "tear pump", simultaneous treatment of nasal complications, et al However, so far, the e cacy of EE-DCR has been reported differently, and its losers are not rare [8][9][10].…”
Section: Introductionmentioning
confidence: 99%